Perlindungan Hukum Bagi Pihak Pemegang Hak Sub Lisensi Terhadap Wanprestasi Dalam Perjanjian Kerjasama Penyiaran - Putri Intan Ayuningutami; Arief Suryono (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
In an agreement, there are often defaults committed by both debtors and creditors. One of the default cases that occurs is a default in a broadcasting cooperation agreement made by a television company. To protect the rights of parties who are harmed by the default that has occurred, there must be legal protection that regulates it. Therefore, this legal research aims to analyse the legal protection given to the sub-license right holder or as the licensor of television broadcast content for default in the broadcasting cooperation agreement made by the broadcast content licensee and then analyse the appropriate dispute resolution to resolve the default. This research uses a prescriptive normative research method with a statutory approach, conceptual approach, and case approach based on the dispute that occurred in Decision Number 08/Haki.Hak Cipta/2015/PN.Niaga.Sby. Based on this legal research, the author concludes that the form of legal protection that can be given to sub-licence rights holders as broadcast content licensors to broadcast content recipients in the event of default is internal and external legal protection with dispute resolution that can be in the form of alternative dispute resolution or the realm of the court applicable in Indonesia.